Transferência internacional de tecnologia universidade-empresa: desafios à luz dos custos transacionais - Spiandorello, Fabíola de Moraes (Universidade Federal de São Carlos, 2019)
Regarding the context of innovation economy, international knowledge transfer can be a real viability for the generation of wealth, playing a significant role in economic and social development of several countries. Establishing university-company contracts comes with it a series of challenges which need to be overcome in order to allow knowledge to flow with less friction between the parties. If such contracting is already complex when both organizations have the same nationality, international transactions have even greater issues. On the other hand, it is an important activity for the institutional development and can provide economic growth to its country. Therefore, the purpose of this study was the transactional costs for the establishment of international university-company contracts, aiming at transferring knowledge from academia to companies. In this study, the dimensions of international technology transfer subject to contractual contingencies were identified and, considering the Transaction Costs Theory, one sought to qualitatively assess which are the most relevant issues for contracting. Using the methodology of Qualitative Comparative Analysis, it was possible to infer which of the transactional elements identified have a correlation with the establishment of international university-company partnerships. Identification of relevant transactional elements was carried out initially through the literature, and later an interview was conducted with a multinational Brazilian company’s innovation manager who carries out international contracting with foreign universities. Subsequently, an electronic survey was drafted and submitted to more than 300 foreign universities. The answers to the survey provided relevant information: it was identified that, related to universities, internationalization and scientific influence (translated in the number of citations) are characteristics that most encourage the establishment of international partnerships with companies. The environment for technology transfer is affected by uncertainties introduced primarily by regulatory and dispute resolution issues; it was identified that the legal system in which the university is immersed does not increase transaction frictions. Furthermore, Intellectual Property Rights are extremely relevant for effective transfer, and preferred contracting modalities involve licensing of these rights, precisely by minimizing information asymmetries between parties. Finally, this work proved to be relevant by bringing to light in a consistent manner the difficulties of contracting – using a powerful but still unknown methodological tool – and what are some suggestions for minimizing these transactional costs.
University-corporate international technology transfer: challenges in the light of transaction costs
Keywords: Transferência de tecnologia; Relação universidade-empresa; Propriedade intelectual; Inovação; Custos de transação; Technology transfer; University-corporate relations; Intellectual property; Innovation; Transaction costs; CIENCIAS SOCIAIS APLICADAS::DIREITO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITOS ESPECIAIS; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::ECONOMIA DE TECNOLOGIA